Uji Aktivitas Antioksidan Ekstrak Etanol Biji Buah Merah (Pandanus Conoideus De Vriese) Asal Kabupaten Poso Sulawesi Tengah - Sulaeha, Siti; Jura, Minarni R.; Rahman, Nurdin (Universitas Tadulako, 2017)
Red fruit seeds have not been studied and known benefits, therefore it needed scientific information about the content and benefits of red fruit seeds. This study aims to analyze the antioxidant power red fruit seed extract as well determining the IC50 value of red fruit seed extract which has the ability of natural antioxidants. Determination of free radical DPPH (1,1-diphenyl-2-picrylhidrazyl) after the addition of red fruit seeds extract is determined using UV-Vis spectrophotometer. Variations in the concentration of the red fruit seed extract used is 20 ppm, 40 ppm, 60 ppm, 80 ppm and 100 ppm.The positive control used is vitamin C with the same concentration. While the negative control using DPPH solution dissolved in absolute ethanol. The results showed IC50 values obtained for the red fruit seed extract and vitamin C are 223.8 ppm and 1.73 ppm. Based on the IC50 data can be known that vitamin C antioxidants more powerful than red fruit seed extract which belongs to natural antioxidants are very weak.